2020
DOI: 10.1002/adfm.202001994
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Chemotherapy of p53‐Mutated Cancer through Ubiquitination‐Dependent Proteasomal Degradation of Mutant p53 Proteins by Engineered ZnFe‐4 Nanoparticles

Abstract: A significant percentage of human cancers harbor missense mutations in the TP53 gene and express highly stabilized mutant p53 protein (mutp53) with tumor‐promoting gain‐of‐function (GOF) properties. Inducing mutp53 degradation is a viable precision anti‐tumor therapeutic strategy. Based on the previously reported finding that a zinc‐curcumin compound induced mutp53 degradation, a series of ZnFe nanoparticles (ZnFe NPs) are synthesized and it is found that ZnFe‐4, with an Zn:Fe ratio of 1:2, exhibits outstandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…In addition, Mn-ZnO 2 NP-induced degradation of mutp53 and wild-type p53 accumulation in MDA-MB-231 cells also caused the cell cycle arrest at the G2M phase ( Fig. S18 ), consistent with previous evidence [ 23 ]. Taken together, the obtained results demonstrated that Mn-ZnO 2 NPs could induce Mutp53 degradation via the released Zn 2+ and ROS, activate WTp53 mainly via the released Mn 2+ , and promote cytotoxic •OH generation via the Fenton reaction, which synergistically eradicated the p53-mutated tumor cells.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, Mn-ZnO 2 NP-induced degradation of mutp53 and wild-type p53 accumulation in MDA-MB-231 cells also caused the cell cycle arrest at the G2M phase ( Fig. S18 ), consistent with previous evidence [ 23 ]. Taken together, the obtained results demonstrated that Mn-ZnO 2 NPs could induce Mutp53 degradation via the released Zn 2+ and ROS, activate WTp53 mainly via the released Mn 2+ , and promote cytotoxic •OH generation via the Fenton reaction, which synergistically eradicated the p53-mutated tumor cells.…”
Section: Resultssupporting
confidence: 90%
“…Following previous studies [ 23 , 34 ], the lysates of MDA-MB-231 cells after the treatment with Mn-ZnO 2 NPs without or with the presence of MG132 (10 μM) for 6 h were subjected to immunoprecipitation with BeaverBeads™ Protein A/G kit (BEAVER Biomedical, Suzhou, China) by using the antibody p53 (DO-1, 1 μg per sample). The pull-down complex was detected by western blotting with mutant p53 (ab32049, 1:1000 dilution), the Ubiquitin (ab134953, 1:1000 dilution) and K48-Ub (ab140601, 1:1000 dilution) antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Furthermore, some metal-based materials with optical and paramagnetic properties can be used as contrast agents to image and track the delivery process of the vaccine. 43 Although the low sensitivity of magnetic resonance (MR) imaging (MRI) using Fe 3 O 4 is one concern for the applications of tumor theranostics, 44,45 doping with zinc ions in Fe 3 O 4 has been explored to improve the paramagnetism of nanoparticles. 43,46 Taking the aforementioned points together, we designed a multifunctional magnetic anticancer nanovaccine that can generate an enhanced CD8 + T-cell response for targeting delivery mediated by an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…43 Although the low sensitivity of magnetic resonance (MR) imaging (MRI) using Fe 3 O 4 is one concern for the applications of tumor theranostics, 44,45 doping with zinc ions in Fe 3 O 4 has been explored to improve the paramagnetism of nanoparticles. 43,46 Taking the aforementioned points together, we designed a multifunctional magnetic anticancer nanovaccine that can generate an enhanced CD8 + T-cell response for targeting delivery mediated by an external magnetic field. Dual adjuvants, including imiquimod and inorganic Zn 1.15 Fe 1.85 O 4 , were coencapsulated in the Pluronic F127 block copolymer.…”
Section: Introductionmentioning
confidence: 99%